PENGARUH LATIHAN QUICKNESS BOX TERHADAPWAKTU REAKSI PADA ATLET PUTRI BELADIRI SHORINJI KEMPO RUMBAI PEKANBARU - Ria Anggelia.S Anggelia; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, This research want to know is there any effect of Quickness Box  exercise toward reaction time in the women athlets martial arts Shorinji Kempo Rumbai Pekanbaru. So as to develop the ability of reactioning time when performing open and close formation at the time of Embu so that no movement tempo chase each other and produce a game tehnique that is neat and well. This research was experimental research. The population in this research was the women athlets martial arts Shorinji Kempo Rumbai  Pekanbaru, while the sample was the women athletes martial arts Shorinji Kempo Rumbai Pekanbaru, the total of 8. Sampling technique used in this research was Total Sampling. According to Ariku